2015
DOI: 10.1002/jmri.25111
|View full text |Cite
|
Sign up to set email alerts
|

Vortex‐ring mixing as a measure of diastolic function of the human heart: Phantom validation and initial observations in healthy volunteers and patients with heart failure

Abstract: Vortex-ring mixing as a measure of diastolic function of the human heart: Phantom validation and initial observations in healthy volunteers and patients with heart failure.Töger, Johannes; Kanski, Mikael; Arvidsson, Per; Carlsson, Marcus; Kovács, Sándor J; Borgquist, Rasmus; Revstedt, Johan; Söderlind, Gustaf; Arheden, Håkan; Heiberg, Einar Link to publication Citation for published version (APA): Töger, J., Kanski, M., Arvidsson, P., Carlsson, M., Kovács, S. J., Borgquist, R., ... Heiberg, E. (2016). Vortex-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…MRI compatible motion systems are much more expensive and this would significantly increase the cost of the phantom. A Magnetic Resonance compatible ring vortex flow has already been demonstrated by Toger et al [27,36], and although the phantom proposed in this paper exploits a comparable technology, our design aspires to be lowcost, compact, portable, easy to manufacture, programmable. Future work will extend the assessment presented here to include comparative studies between medical imaging modalities (Ultrasound, CT, and with some adaptation MRI) and optical modalities (Laser-PIV, Laser-diode) to further assess reliability, long-term stability and detailed flow performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI compatible motion systems are much more expensive and this would significantly increase the cost of the phantom. A Magnetic Resonance compatible ring vortex flow has already been demonstrated by Toger et al [27,36], and although the phantom proposed in this paper exploits a comparable technology, our design aspires to be lowcost, compact, portable, easy to manufacture, programmable. Future work will extend the assessment presented here to include comparative studies between medical imaging modalities (Ultrasound, CT, and with some adaptation MRI) and optical modalities (Laser-PIV, Laser-diode) to further assess reliability, long-term stability and detailed flow performance.…”
Section: Discussionmentioning
confidence: 99%
“…The ring vortex flow is well suited to its role as a reference flow because it offers characteristics like stability, predictability, reproducibility and controllability [20,21,26,27] [1,2,8,28,29,30,31,32,33,34,35,36]. Vortex rings are natural fluid phenomena that are known to balance flow within the chambers of the heart or may be observed in the presence of vessel bifurcations or pathological conditions, such as stenosis and aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…; Töger et al. ). Atrial tissue characterization has recently become feasible noninvasively using an MRI method for visualizing fibrosis as LA late gadolinium enhancement (LGE) (McGann et al.…”
Section: Introductionmentioning
confidence: 96%
“…Most studies have assessed LVDD and LV diastolic filling by quantitative analysis of intra‐ventricular vortex derived from MRI echo or VFM. Töger et al validated quantified vortex‐ring mixing as a novel potential index of diastolic dysfunction using MRI (4D‐Flow). Kheradvar et al found that patients with different patterns of LV diastolic filling had marked changes in LV vortex formation time.…”
Section: Introductionmentioning
confidence: 99%